Impact of renin–angiotensin system inhibitors use on mortality in severe COVID-19 patients with hypertension: a retrospective observational study. Issue 12 (December 2020) - Zhong, Yanjun; Zhao, Lishu; Wu, Guobao; Hu, Chunhong; Wu, Chenfang; Xu, Min; Dong, Haiyun; Zhang, Quan; Wang, Guyi; Yu, Bo; Lv, Jianlei; Wu, Chao; et al.
Objective: Association of angiotensin-converting enzyme inhibitors (ACEI) or angiotensin receptor blockers (ARB) use with coronavirus disease 2019 (COVID-19) remains controversial. We aimed to investigate the impact of ACEI/ARB use on all-cause mortality in severe COVID-19 patients with hypertension. Methods: We enrolled 650 COVID-19 patients from Changsha and Wuhan city between 17 January 2020 and 8 March 2020. Demographic, clinical characteristics, and outcomes were collected. Multivariable analysis and propensity-score matching were performed to assess the impact of ACEI/ARB therapy on mortality. Results: Among the 650 patients, 126 who had severe COVID-19 concomitant with hypertension were analyzed. The average age was 66 years and 56 (44.4%) were men. There were 37 ACEI/ARB users and 21 in-hospital deaths (mortality rate, 16.7%). Male sex (odds ratio [OR], 5.13; 95% confidence interval [CI], 1.75 to 17.8), but not ACEI/ARB use (OR, 1.09; 95%CI, 0.31 to 3.43), was an independent risk factor for mortality in severe COVID-19 patients with hypertension. After propensity-score matching, 60 severe COVID-19 patients were included and no significant correlation between use of ACEI/ARB and mortality was observed. Conclusions: There was no significant association of ACEI/ARB use with mortality in severe COVID-19 patients with hypertension. These findings support the continuation of ACEI/ARB therapy for such patients.